Desain Canva Sebagai Media Promosi Usaha Mikro dan Media Informasi di Desa Bantarsari - Gustian Rama Putra; Arie Qurania; Yusma Yanti; Puspa Citra; Syarif Hidayatullah; Hermawan Hermawan; Victor Ilyas Sugara; Asep Saepulrohman; Agung Prajuhana Putra; Kotim Subandi; Adriana Sari Aryani; I Wayan Sriyasa (Journal of Engineering and Information Technology for Community Service, 2023)
Digital information media in this era has very good potential, especially in developing micro-businesses to introduce their products, besides that information media is also needed to provide education and information to socialize, this is very necessary for the government in the district to develop village results and information that can be conveyed clearly to the community. Community service carried out by the Computer Science Study Program of Pakuan University aims to provide training to village office staff and junior and senior high school students in Bantarsari Village to be able to apply Canva as a medium for promoting micro-business and related information media, socialization, disaster prevention, appeals and other notifications in Bantarsari Village